PENGARUH MODAL KERJA TERHADAP ROI STUDI KASUS PERUSAHAAN RITEL DI BURSA EFEK INDONESIA - Herlina Ferliyanti (Yayasan Akrab Pekanbaru, 2018)
Working Capital management is critical in the survival of the company. Good working capital management resulted in profits for the company. The funds are available for use the daily operations is called the working capital. Working capital used to buy raw material, pay salaries, transportations cost, and so forth. The analysis method used is multiple regression (Multiple Linear Regression). The results indicate the presence of element such as liquidity, activity, and the risk that simultaneously affect the Return on Investment. Showed partial liquidity variable and the most influential activities that can be explained by the adjusted R2 value of 77% while the rest 23% influenced by other variable which is not explained by this research model. The results of regression analysis obtained in this research was Y = 37.757 + 0.020X1 + 7.753X2 – 0.122X3, meaning that the liquidity variables and the activity has a positive influence on the return on investment.The analysis is based on hypothesis test showed t test obtained values tcount 1.43, meaning that the smaller the liquidity and activity, the greater on the return on investment is obtained. T test result prove that the hypothesis is proven true Ha2. F test results obtained Fcount > Ftable (22.165 > 2.71), meaning that there is significant influence between liquidty, activity, and the risk of simultaneous Return on Investment. F test results (Ha1). Based on the analysis, the most dominant elements influencing in working capital is a liquidity and activity variable. Keyword : Working Capital, Liquidity, Activity, Risk.